2010
DOI: 10.1007/s11104-010-0368-4
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast microsatellites reveal that metallicolous populations of the Mediterranean shrub Cistus ladanifer L have multiple origins

Abstract: Cistus ladanifer L. (Cistaceae) is a Mediterranean shrub covering different kinds of soils in the Western Mediterranean area. This species has colonised several metalliferous areas (serpentine outcrops as well as human-polluted sites) throughout its distribution range, and is therefore an interesting species to study the possible effects on genetic diversity and differentiation produced by the colonisation of areas polluted with heavy metals. The genetic structure of 33 natural populations distributed across i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
(69 reference statements)
0
11
1
1
Order By: Relevance
“…However, no differences in genetic diversity between metallicolous and nonmetallicolous populations have been consistently found in the species investigated to date (Vekemans and Lefèbvre, 1997;Quintela-Sabarís et al, 2010), such as A. halleri (Pauwels et al, 2005), A. bertolonii (Mengoni et al, 2003) and M. laricifolia ssp. ophiolitica (Moore et al, 2013), and neither have they been found here (Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…However, no differences in genetic diversity between metallicolous and nonmetallicolous populations have been consistently found in the species investigated to date (Vekemans and Lefèbvre, 1997;Quintela-Sabarís et al, 2010), such as A. halleri (Pauwels et al, 2005), A. bertolonii (Mengoni et al, 2003) and M. laricifolia ssp. ophiolitica (Moore et al, 2013), and neither have they been found here (Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…The observation of multiple origins of tolerant populations has raised the question of whether or not all individuals of a given species are equally capable of growing on these soils (Westerbergh ; Quintela‐Sabarís et al . ). However, physiological or morphological differentiation leading to greater tolerance of serpentine or heavy metals in the populations growing on these soils has been demonstrated in several studies (Yokoo et al .…”
Section: Introductionmentioning
confidence: 97%
“…Serpentine specialists are often smaller, flower earlier and have smaller or otherwise less conspicuous flowers than their relatives on normal soils (Macnair & Gardner ; Baldwin ; O'Dell & Rajakaruna ). With the exception of the high magnesium concentration, other metalliferous soils, such as those derived from mine tailings, present many of the same challenges as do serpentine soils (Macnair & Gardner ), and many serpentine‐tolerant species have been able to expand onto mine tailings when this habitat became available (e.g., Cistus ladanifer , Quintela‐Sabarís ; Silene paradoxa , Mengoni et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also results for vascular plants are not always supportive. Quintela-Sabarís et al (2010) and Kolář et al (2014b) report no evidence of genetic differentiation between serpentinite and non-serpentinite populations of target vascular plants. Kolář et al (2014a), by contrast, report Mg stress as an adaptive character of Knautia arvensis.…”
Section: Magnesium Toxicity As An Evolutionary Trigger For Wetland Brmentioning
confidence: 98%